Aprepitant in a Multimodal Approach for Prevention of Postoperative Nausea and Vomiting in High-Risk Patients: Is There Such a Thing as "Too Many Modalities"?. (2009) - Hache, John J.; Vallejo, Manuel C.; Waters, Jonathan H.; Williams, Brian A.
Abstract : Postoperative and postdischarge nausea and vomiting (PONV and PDNV, respectively) add morbidity to perioperative outcomes. Combining some antiemetic agents of different mechanisms is more effective than using single agents, although this concept has not yet been tested extensively with aprepitant. Consecutive high-risk patients for PONV (n = 100) were given preoperative aprepitant 40 mg before surgery and were followed perioperatively. Female patients receiving general anesthesia (n = 81) were selected for data analysis. The primary endpoints were PONV/PDNV in the 48 h after surgery. For patients included in the data analysis, using Apfel PONV risk factors, the median risk count was four out of four. PONV and PDNV incidences were 21% (95% CI: 14-31%) and 37% (95% CI: 27-48%), respectively. Two patients experienced PACU (postanesthesia care unit) vomiting and two patients experienced emesis postdischarge. When using regression modeling and comparing patients who received one or two vs. three or four mechanistically unique antiemetics (added to preoperative aprepitant), while adjusting for surgical case duration, the three or four additional antiemetic group showed more PONV/PDNV (Odds Ratio 3.73, 95% CI 1.3-10.9, p = 0.016) than did the one or two additional drug group. There were no other predictors of PONV/PDNV (transabdominal surgery, four vs. three Apfel risk factors) in these patients. The low incidence of vomiting (2-5%) suggests the potential importance of aprepitant in a multimodal antiemetic regimen. However, there may be the potential that too many unique antiemetic mechanisms combined with preoperative aprepitant may actually increase the incidence of perioperative nausea.